Pengaruh Electronic Word of Mouth Terhadap Keputusan Pembelian Di Toko Zhalsa.Id Melalui Shopee - N Nursavira; Nurainun Nurainun (Jurnal Visioner & Strategis, 2022)
This study examined the effect of electronic word of mouth, consisting of dimensions (intensity, valance of opinion, and content) on purchasing decisions at the Zhalsa.id store on Shopee. This study used primary data obtained by distributing questionnaires to 112 respondents who were selected using the purposive sampling method. The data analysis method used was the multiple linear regression method with the help of SPSS 24. This study showed that intensity significantly influenced purchasing decisions at Zhalsa.id store on through Shopee, valance of opinion significantly influenced purchasing decisions at Zhalsa.id stores on Shopee and content significantly influenced purchasing decisions at the Zhalsa.id store on Shopee. Simultaneously, intensity, valance of opinion, and content significantly influenced purchasing decisions at the Zhalsa.id store on Shopee.